TO DETERMINE THE FEATURES OF THE COURSE OF PREGNANCY AND CHILDBIRTH WITH ANTENATAL RUPTURE OF AMNIOTICS (Modern education and development, 2024)
Childbirth due to premature rupture of membranes is often accompanied by abnormalities of labor, hypo- and atonic bleeding, high rates of trauma to the soft tissues of the birth canal, disruption of uteroplacental circulation and the development of fetal hypoxia.